The Role of Social Media in the ISIL-West Crisis: A Technoethical Analysis of Twitter - McHugh, Laura (Université d'Ottawa | University of Ottawa, 2015)
This research paper investigates the role of social media platforms during the ISIL-West crisis. The crisis emerged due to the clash between the ideologies of ISIL and “the West”, resulting in manageable, but unresolvable competing interactions. The increasing use of social media within today’s society has prompted the opportunity to further understand the role of crisis communication. This study identifies insights into the crisis communication process that is facilitated through Twitter. The theory of technoethics is utilized to assess the ethical conduct of these communicative activities as a crisis unfolds; ultimately examining the ways that social media communication conforms to ethical standards. Based on a qualitative content analysis of 200 tweets relating to the ISIL-West crisis, the findings uncover the strategies employed by Twitter users in disseminating various types of crisis communication information online. As well, the findings discuss the perceived trustworthiness of Twitter users, and the level of ethicality used to conduct crisis communication pertaining to the ISIL-West crisis. These findings provide valuable insights into the way society discusses and engages in a crisis through social media outlets, leading to new opportunities to explore communication intentions and practices through technology channels.